PELAKSANAAN KETENTUAN HUKUM YANG MENGATUR RUANG TERBUKA HIJAU DI KOTA PALEMBANG : The Implementation of Legal Provisions Govering Green Open Space in Palembang City - Khotimah, Rahadeva Khuznul; Hasni (Faculty of Law, Universitas Trisakti, 2024)
The assessment is based on Law No. 26 Year 2007, which states public green spaces cover at least 20% of the urban area. Therefore, the Palembang City Regional Regulation expands green spaces by building green spaces in Palembang City. The problem is the proportion of green space in Palembang City to achieve the minimum area of public green space in Palembang City based on Law No. 26 of 2007 and Regional Regulation No. 15 of 2012 of Palembang City. The city area plan 2012-2032 and the limitations that are challenges faced by the local government in the implementation of RTH development in Palembang City. Normative legal and analytical descriptive research is the type of research while the conclusion was done using deductive logic. The concrete result is that the green area of Palembang City does not reach the 20 percent portion. Therefore, the Palembang City Government will continue to implement the improvement of green open space in Palembang City by Law Number 26 of 2007 and Palembang City Regional Regulation Number 15 of 2012. The obstacles experienced by the local government in the management to build RTH in Palembang City are still a lot of private land ownership, the need to conduct a study or master plan that involves many parties and a lack of funds for RTH Development. It would be nice if the Palembang City Government paid more attention to the existence of public green open spaces in Palembang City.